Visight Shield Sdn Bhd / Noor Syahirah Abu Samat ... [et al.] - Abu Samat, Noor Syahirah; Zamrin, Nor Azryna; Rosnan, Muhammad Izzat; Shahrul Zahri, Muhammad Nor Azizi (2019)
Visight Shield Sdn. Bhd. is the security services company that are expert in supply and install Closed Circuit Television (CCTV) and Security Alarm System. The business was located Taman Dagang, Ampang Jaya, Selangor and was conducted by five person of people. The team was divided by four sections which is operation, finance, marketing, and administration and monitor by the General Manager to make sure the business going smoothly as planned. The concept of the business is to provide safety and security to customer especially society.